Analysis of the Effect of Financial Ratios on Profit Growth - Rafidah Saleh; Arifuddin Mannan; Andi Aswan (Hasanuddin Journal of Business Strategy, 2022)
This study aims to determine whether the Current Ratio (CR), Debt to Asset Ratio (DAR), and Total Asset Turn Over (TATO) have an effect on earnings changes. The data used in this study is time-series data (time series) of PT Industrial Estate of Makassar from 2016 to 2020 which is processed on a quarterly basis. Data analysis in this study used multiple linear regression. Different from the existing studies, the Current Ratio (CR) had affected negatively, but insignificantly profit growth. This strengthens the fact that unlike banking and other categories called the high liquidity group, they depend mostly on liquidity. An industrial estate company, especially those in the stable stage, but not in the growth phase, its CR did not affect profitability. The study also found that the Debt to Asset Ratio (DAR) and the Total Assets Turnover (TAT) affect positively and significantly profit growth.